P96 The regulation and pharmacological modulation of immune complex induced production of type III IFN by plasmacytoid dendritic cells. (23rd March 2020) - Hjorton, Karin; Hagberg, Niklas; Pucholt, Pascal; Berggren, Olof; Eloranta, Maija-Leena; Rönnblom, Lars
Abstract : Background: Acknowledging the importance of type I interferon (IFN) in Systemic Lupus Erythematosus (SLE), we asked if RNA containing immune complexes (RNA-IC), which trigger the IFN-α synthesis by plasmacytoid dendritic cells (pDCs), also activate type III IFN (IFN-λ1-3) production, and how this is regulated. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from SLE patients and healthy individuals and depleted of monocytes. Immune cells were isolated from healthy PBMCs. Cells were stimulated with RNA-IC. Cytokines were measured by immunoassays, a microarray of pDCs, NK and B cells, as well as single-cell RNA-sequencing of pDCs was performed. Results: Type III IFN mRNA was induced in RNA-IC stimulated pDC-NK and pDC-B cell co-cultures, type III IFN was produced in pDC and pDC-NK cell co-culture supernatants. A small subset (3%) of RNA-IC activated pDCs expressed both IFNs type III and type I. Priming with IFN-λ2, IFN-α2b, interleukin (IL)-3, IL-6 and granulocyte-macrophage colony stimulating factor (GM-CSF) significantly enhanced IFN-λ1/3 production by 2–5 fold. In pDC-NK cell co-cultures from SLE patients, IFN-α2b and GM-CSF increased the proportion of RNA-IC responding IFN-λ1/3 producing individuals from 9% to 36%. Hydroxychloroquine as well as an interleukin receptor 1 associated kinase 4 inhibitor (IRAK4i) significantly inhibited the RNA-IC-triggered IFN-λ1/3 production by pDCs and pDC-NK cell co-cultures by >90%. Conclusions: Type III IFN production in a small subset of pDCs can be triggered by RNA containing IC, enhanced by NK cells and several pro-inflammatory cytokines, and inhibited by blocking the TLR-MyD88 pathway, resembling the regulation of type I IFN. Thus, our results support a contributing role for both type I and type III IFN in SLE, which needs to be considered when targeting the IFN system in this disease.